1998
DOI: 10.1266/ggs.73.173
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of carbon ion-induced mutations in Arabidopsis thaliana.

Abstract: In order to elucidate the characteristics of the mutations induced by ion particles at the molecular level in plants, mutated loci in carbon ion-induced mutants of Arabidopsis were investigated by PCR and Southern blot analyses. In the present study, two lines of gl1 mutant and two lines of tt4 mutant were isolated after carbon ion-irradiation. Out of four mutants, one had a deletion, other two contained rearrangements, and one had a point-like mutation. From the present result, it was suggested that ion parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
36
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 23 publications
1
36
0
3
Order By: Relevance
“…Although low-energy ion-beam implantation has obvious benefits, such energy can induce mutagenesis, injury, and plant death . Low-energy ion-beam irradiation can cause nuclear and chromosomal defects, resulting in DNA deletions, duplications, and transposition of DNA fragments (Shikazono et al, 2001;Feng et al, 2007;Ya et al, 2010). Other plant responses to ion-beam irradiation include oxidative stress, free radical generation, and changes in signal transduction, such as long-distance transfer of radiation effect signals and alterations in the abscisic acid signal pathway (Feng et al, 2006;Chen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although low-energy ion-beam implantation has obvious benefits, such energy can induce mutagenesis, injury, and plant death . Low-energy ion-beam irradiation can cause nuclear and chromosomal defects, resulting in DNA deletions, duplications, and transposition of DNA fragments (Shikazono et al, 2001;Feng et al, 2007;Ya et al, 2010). Other plant responses to ion-beam irradiation include oxidative stress, free radical generation, and changes in signal transduction, such as long-distance transfer of radiation effect signals and alterations in the abscisic acid signal pathway (Feng et al, 2006;Chen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, research on ion-beam implantation focused on the immediate cause of the mutagenesis (Shikazono et al, 2001;Maekawa et al, 2003;Yamaguchi et al, 2003). The molecular mecanism of generational effects of ion-beam irradiation is seldom investigated because first-generation biological effects are rarely inherited by subsequent generations.…”
Section: Introductionmentioning
confidence: 99%
“…This technique is very effective at causing mutations in embryos at a particular stage of fertilization, without damaging other plant tissues (Abe et al 2002). Moreover, heavy ion irradiation, which induces a broad spectrum and high frequency as well as high diversity of mutants, has shown a great potential for breeding cultivars (Shikazono et al 2001;Tanaka et al 2010). Existing studies have demonstrated that ion irradiation caused irreparable DNA double-strand breaks (DSB), whereas most damage caused by traditional radiation resources (like X-ray and γ-ray) was repaired (Wada et al 2002).…”
mentioning
confidence: 99%
“…Damage that cannot be easily repaired is vital for mutant induction, and is a major contributor to the high relative biological effectiveness and dominates the biological consequences in plants (Feng et al 2006). Biological effects of high-LET heavy-ion radiation are more pronounced than those of X-rays, γ-rays, and electron beams (Shikazono et al 2001). Mutation doi: 10.17221/214/2014-CJGPB in plant is an effectual tool to create new breeding varieties and has been widely used in recent years (Feng et al 2006;Roychowdhury & Tah 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation